An Analysis of Reduction Technique Applied on the Interrogative Sentences and Its Impact on the Translation Quality in the Movie Subtitle of National Treasure 2: Book of Secret - Siti Noor aisyiyah (Universitas Sebelas Maret, 2023)
This research is conducted to analyze the use of reduction technique on interrogative sentences in the movie subtitle of National Treasure 2: Book of Secret. The objectives of this research are (1) to find out the types of reduction technique in translating interrogative sentences in the movie subtitle of National Treasure 2: Book of Secret: (2) to find out the accuracy and acceptability of the interrogative sentences that are translated using reduction technique in the movie subtitle of National Treasure 2: Book of Secret as a result of the reduction technique application.This research is a descriptive qualitative research. The data consist of interrogative sentences with reduction technique that are found in the movie subtitle National Treasure 2: Book of Secret and the statement from the informants about the quality of the translation. The sampling techniques are total sampling and a purposive sampling technique.The result of this study shows that there are 62 data (52.54%) accurate, 51 data (43.22%) less accurate, and five data (4.23%) inaccurate. The current study also shows that there are 111 data (94.06%) classified into acceptable translations and seven (5.93%) classified into less acceptable translations. Keywords: reduction, reduction techniques, translation quality.